2010
DOI: 10.1111/j.1756-185x.2009.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin‐A and interleukin‐18 levels in ankylosing spondylitis

Abstract: Fetuin-A and IL-18 levels seem to be increased in AS patients regardless of disease activity and treatment type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
(57 reference statements)
2
17
3
Order By: Relevance
“…However, we did not detect any correlation between BASRI and fetuin-A. In contrast to previous studies reporting high fetuin-A levels in AS patients, 10 we found low fetuin-A levels similar to studies in RA and FMF patients. 5,17,18 In addition, the negative correlation we showed between CRP and fetuin-A, and the negative correlation with ESR and CRP demonstrated in studies involving chronic kidney failure, cardiovascular disease, and rheumatic diseases indicate that fetuin-A may be a negative acute phase reactant.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…However, we did not detect any correlation between BASRI and fetuin-A. In contrast to previous studies reporting high fetuin-A levels in AS patients, 10 we found low fetuin-A levels similar to studies in RA and FMF patients. 5,17,18 In addition, the negative correlation we showed between CRP and fetuin-A, and the negative correlation with ESR and CRP demonstrated in studies involving chronic kidney failure, cardiovascular disease, and rheumatic diseases indicate that fetuin-A may be a negative acute phase reactant.…”
Section: Discussioncontrasting
confidence: 56%
“…However, we found no correlation between fetuin-A and disease markers such as ESR, BASDAI, BASFI or BASMI. In contrast to Sarı et al, 10 we also assessed patient BASRI indices. However, we did not detect any correlation between BASRI and fetuin-A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, available data on this subject are still limited and additional information is required to clarify the underlying mechanisms of new bone formation in AS. In a recent study, we reported increased serum fetuin-A levels compared with controls 4. Considering the role of fetuin-A in the regulation of calcified matrix metabolism 5, we designed this study with the primary objective of comparing the fetuin-A levels in AS patients with and without syndesmophytes versus healthy controls.…”
Section: Introductionmentioning
confidence: 99%